Simplify 3 - (4x - 5) + 6.

Responses

1 answer

To simplify the expression 3 - (4x - 5) + 6, we can start by simplifying the expression inside the parentheses:

-(4x - 5) = -4x + 5

Now we can substitute this simplified expression back into the original expression:

3 - (4x - 5) + 6 = 3 - 4x + 5 + 6

Next, we can combine like terms:

3 - 4x + 5 + 6 = (3 + 5 + 6) - 4x

Simplifying further:

(3 + 5 + 6) - 4x = 14 - 4x

Therefore, the simplified expression is 14 - 4x.
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions